UNDERSTANDING THE CONCEPT OF PSEUDOMONAS AERUGINOSA BASIC RESISTANCE MECHANISMS AND IMPACT ON CYSTIC FIBROSIS PATIENTS - Mohammed, Ghaith R (International Journal of Research -GRANTHAALAYAH, 2024)
Numerous human illnesses, mostly connected to healthcare providers, are linked to Pseudomonas aeruginosa. It is linked to antibiotic resistance in hospitals, which makes treatment extremely difficult. However, biofilm-related P. aeruginosa infections provide one of the most difficult treatment problems. The intricate structure of the P. aeruginosa biofilm adds to the pathogenicity of this microbe by causing it to evade the immune system, cause persistent infections that are hard to treat, and result in treatment failure. We looked at a number of molecular facets of P. aeruginosa biofilm pathogenicity. It is believed that anaerobic circumstances, bacterial quorum-sensing systems, and environmental factors in the cystic fibrosis airway all contribute to the production of biofilms in the lung. In order to favor either acute infection or chronic colonization, P. aeruginosa has regulatory mechanisms that are sensitive to environmental signals. Respiratory tract-dwelling P. aeruginosa develop mutations that promote long-term colonization. P. aeruginosa biofilm development is changed by azithromycin, a macrolide that has therapeutic benefits for cystic fibrosis. Among the promising novel treatments that target the production of biofilms are compounds that interfere with quorum sensing.